Marta is solving the equation S = 2πrh + 2πr2 for h. Which should be the result?

By Allen Kazadi
1 Min Read

Marta is solving the equation S = 2πrh + 2πr2 for h. Which should be the result?

StartFraction S Over 2 pi r EndFraction equals h. – r = h
StartFraction S minus r Over 2 pi r EndFraction equals h. = h
S – S minus StartFraction r Over 2 pi EndFraction equals h. = h
S – S minus StartFraction 2 pi Over r EndFraction equals h. = h

Answer:

(S-2πr^2)/ 2πr = h

Step-by-step explanation:

S = 2πrh + 2πr^2

Subtract 2 pi r^2 from each side

S-2πr^2  = 2πrh + 2πr^2 -2πr^2

S-2πr^2  = 2πrh

Divide each side by 2 pi r

(S-2πr^2)/ 2πr = 2πrh/2πr

(S-2πr^2)/ 2πr = h

Follow:
Allen is a Technology guy, He basically works on Top articles related to Technology, Gadgets, and more. To know more about his work.